Listen to your heart: a critical analysis of popular cardiology podcasts - Kamalanathan, Harish; Hains, Lewis; Bacchi, Stephen; Martin, Wrivu N.; Zaka, Ammar; Slattery, Flynn; Kovoor, Joshua G.; Gupta, Aashray K.; Psaltis, Peter; Kovoor, Pramesh (Frontiers in Medicine, 2024)
Purpose Podcasts are an increasingly popular medium for medical education in the field of cardiology. However, evidence suggests that the quality of the information presented can be variable. The aim of our study was to assess the quality of the most popular cardiology podcasts on existing podcast streaming services, using tools designed to grade online medical education. Results We analyzed the five most recent episodes from 28 different popular cardiology podcasts as of 20th of September, 2022 using the validated rMETRIQ and JAMA scoring tools. The median podcast length was 20 min and most episodes were hosted by professors, subspecialty discussants or consultant physicians (87.14%). Although most episodes had only essential content (85%), only a small proportion of episodes provided detailed references (12.9%), explicitly identified conflicts of interest (30.7%), described a review process (13.6%), or provided a robust discussion of the podcast's content (13.6%). We observed no consistent relationship between episode length, seniority of host or seniority of guest speaker with rMETRIQ or JAMA scores. Conclusions Cardiology podcasts are a valuable remote learning tool for clinicians. However, the reliability, relevance, and transparency of information provided on cardiology podcasts varies widely. Streamlined standards for evaluation are needed to improve podcast quality.